FACTORS AFFECTING THE INCOME OF THE SMALL FURNITURE INDUSTRY IN KENDARI CITY - Tajuddin, Tajuddin; Asizah, Nur (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
The furniture industry has a fairly good development, so it will affect the income level of the craftsmen. The purpose of the study was to analyze the effect of capital, labor and total production on income. The research location is in Baruga District, Kendari City. The research focuses on the income of furniture industry entrepreneurs and the factors that influence it. The sample was selected using the census method, namely using the entire population as a sample. The sample was 36 wood industry entrepreneurs. The data analysis technique used is multiple linear regression. The results showed that 1) Jointly business capital, labor, and production on furniture business income in Baruga District, Kendari City have a significant effect on furniture business income. This is indicated by the test results Fhitung = 14.935 > ? = 0.05. (2) Business capital on furniture business income in Baruga Subdistrict, Kendari City has a significant effect on increasing the income of respondents' furniture business spread across Baruga Subdistrict, Kendari City. This is indicated by the results of the t test at the level of sign. 0.128 > ? = 0.05., (3) The number of workers on the income of the furniture business in Baruga District, Kendari City does not have a significant effect on increasing the income of the furniture business spread across Baruga District, Kendari City. This is indicated by the results of the t-test at the level of sign. 0.000> ? = 0.05 and (4) Furniture business production (x3) partially does not have a significant effect on increasing the income of furniture businesses scattered in Baruga District, Kendari City. This is indicated by the results of the t test at the sign level. 1,954 > ? = 0,05. This means that capital, labor, and total production simultaneously have a significant effect on the income of wood furniture industry entrepreneurs. Capital, labor, and raw materials partially have a positive and significant effect on the income of wood furniture industry entrepreneurs. This means that the greater the capital spent, the labor used and the amount of production owned, the greater the possibility of the amount of production produced, so that the income received is greater.